Effects of Prolonged Starvation on Cholesterol Content of Gonads in Clarias batrachus - Prasad, Nayan Kumar (Our Nature, 2015)
Starvation is experienced in most species of fish during certain periods of every year largely due to environmental conditions and it affects different organs in different ways. The present paper deals with the impact of starvation on cholesterol content of gonadal tissues of a fresh water catfish, Clarias batrachus. The level of cholesterol in the gonads has been found higher in female than in male under both the normal and starved conditions. Both the male and female gonads showed non-significant depletion up to 20 days of starvation but thereafter, it was sharp. After 40 days of starvation, the cholesterol depleted about 84% in male and 79% in female of their normal values. Our Nature (2015), 13(1): 26-30